The influence of gate start position on physical performance and anxiety perception in expert BMX athletes - Di Rienzo, F.; Martinent, G.; Levêque, L.; MacIntyre, T.; Collet, C.; Guillot, A. (Journal of Sports Sciences, 2018)
The critical importance of the start phase in bicycle motocross (BMX) racing is increasingly acknowledged. Past experiments underlined that the internal lane of the starting gate provides a strong positional advantage. However, how lane position affects start performance and cognitive and somatic state anxiety remains unexplored. We examined the start performance and anxiety responses of youth national-level BMX riders in both experimental and ecological contexts. We used contextualization motor imagery routines to evaluate start performance and state anxiety from the internal and external lanes. Cycle ergometer measures revealed a better start performance from the external lane, but we did not record any lane effect on actual gate start times. Both somatic and cognitive anxiety scores were higher before racing from the internal compared to the external lane. Finally, state anxiety (i.e., somatic anxiety, worry and concentration disruptions) negatively predicted the start performance. Present findings provide original insights on psychological factors involved in BMX start performance, and might contribute to fruitful coping interventions and training programmes in sports overlapping the framework of "handicap races" taking the specific form of positional advantages/disadvantages at the start (e.g., ski/snowboard cross, athletics, swimming, motorsports, etc.).